2014
DOI: 10.1002/tcr.201402021
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Local Atomic Manipulation on Semiconductor Surfaces in the STM: The Case of Chlorobenzene on Si(111)‐7×7

Abstract: Control over individual atoms with the scanning tunnelling microscope (STM) holds the tantalising prospect of atomic-scale construction, but is limited by its "one atom at a time" serial nature. "Remote control" through non-local STM manipulation-as we have demonstrated in the case of chlorobenzene on Si(111)-7×7-offers a new avenue for future "bottom-up" nanofabrication, since hundreds of chemical reactions may be carried out in parallel. Thus a good understanding of the non-local manipulation process, as pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 32 publications
(47 reference statements)
1
20
0
Order By: Relevance
“…We take τ D =200 fs [36] and so convert the β values of figure 4 to the total probability of manipulation per injected electron N as displayed in figure 5(c). This form of analysis should be identical to the original 'scanning' manipulation work and indeed we find our results here match qualitatively and quantitatively with that earlier work [32,39]. Figure 5(c) shows the voltage dependence of both the probability per electron of molecular displacement and the probability per electron of photon emission.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…We take τ D =200 fs [36] and so convert the β values of figure 4 to the total probability of manipulation per injected electron N as displayed in figure 5(c). This form of analysis should be identical to the original 'scanning' manipulation work and indeed we find our results here match qualitatively and quantitatively with that earlier work [32,39]. Figure 5(c) shows the voltage dependence of both the probability per electron of molecular displacement and the probability per electron of photon emission.…”
Section: Discussionsupporting
confidence: 85%
“…The main difference is whereas desorption of toluene is an irreversible process, the manipulated silicon adatoms are meta-stable at room temperature and drop back to their original sites before they can be imaged by an STM. We have also reported that the low lying state at ∼+0.5 V is reduced in intensity but still present at the location of the bonding adatom to a chlorobenzene adsorbate [32]. Toluene and chlorobenzene both bond and are manipulated in near identical fashion on the Si(111)-7×7 surface.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Both, STM-induced desorption [22] and dissociation [23] of the carbon-chlorine-bond, have been reported in experiments at room temperature. Desorption can be induced by electrons or holes (positive or negative bias voltage) and was found to be largely non-local [8,24]. We characterised physisorbed and chemisorbed chlorobenzene using a cluster approach and density functional theory (DFT) in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Desorption [15] of chlorobenzene from a Si(111)-7x7 surface can be induced in a one-electron (positive surface bias voltage) or a one-hole process (negative bias voltage) and is to a large extent non-local [13,16]. Also dissociation of the carbon-chlorine-bond has been reported either in a two-electron process [17] or a thermally assisted one-electron process [18].…”
mentioning
confidence: 99%